Bibliometric Analysis of Student Politeness in Global Education Literature - Nelissa, Zahra; Agus Taufiq; Juntika Nurihsan; Anne Hafina Adiwinata; Fatimah Nooh (G-Couns: Jurnal Bimbingan dan Konseling, 2025)
Politeness is a social character that involves self-control and mutual respect, serving as a behavioral guide to build positive interactions in the educational environment. This research aims to examine publication patterns, geographical distribution, and the main topics addressed in studies on student politeness. The methodology used is bibliometric analysis with data taken from the research database sourced from the Scopus database within the range of 2014 to 2024. subject area in Social Sciences 786, Art and Humanities 668, Psychology 165. The articles selected and analyzed based on bibliometric indicators, such as the number of publications, amounted to 881. Software analysis was used to identify the keywords "politeness in education" OR "student politeness" OR "politeness" in the Scopus database and analyzed using VOSviewer. The results of this study are expected to support the development of character education programs and improve student-teacher relationships to foster a better educational culture. Keywords: student politeness, character education, bibliometric analysis